From Gender Identity Oppression to Power Reversal in the Novel Calabai - I Gusti Ayu Agung Mas Triadnyani (Humaniora, 2018)
Recently, the sociocultural problems of transgender have shown an increase. The novel, Calabai, vividly depicts various acts of violence perpetrated by Bugis tribesmen against transgender members of the community. They consider transgender as deviant or different. From a humanist perspective, this view forms a violation of the principles of human rights. Actually, this novel develops the idea of cultural identity. Through deconstructive analysis according to Derrida, this study exposes the ideology embedded within such a textual representation of transgender. It reaches two conclusions. First, a reversal of ideology takes place in the text; from oppression based on discrimination, to a power reversal. Second, being regarded as a human being and receiving respect from another human being become a form of recognition of personal and cultural identity.